FRI0198 Usability and safety of SB5 (an adalimumab biosimilar) pre-filled syringe and pre-filled pen in patients with rheumatoid arthritis. (15th June 2017) - Ghil, J; Niebrzydowski, J; Zielińska, A; Lee, Y
Abstract : Background: SB5 is developed as a biosimilar of the reference adalimumab (ADL). Equivalence in pharmacokinetics (PK) and efficacy between SB5-pre-filled syringe (PFS) and ADL-PFS has been demonstrated in a phase I and phase III study. 1, 2 The PK equivalence between SB5-PFS and SB5-pre-filled pen (PFP) in healthy subjects has been reported previously. 3 Objectives: To compare the usability and safety of SB5-PFS and SB5-PFP from a phase II study. Methods: This was an open-label, single-arm study in patients with rheumatoid arthritis (RA). Patients with RA self-administered a total of 6 injections of 40 mg SB5 every other week; the first two injections were through PFS and the following four injections were through PFP. The primary objective of this study was to demonstrate comparability between PFS (at week 2) and PFP (at week 6) in terms of injection site pain score. Patients completed a pain evaluation questionnaire using an 11-point numeric rating scale at two time points (immediately and 15–30 minutes post-injection) after the first four injections. Equivalence between PFS and PFP was concluded if the 97.5% confidence interval (CI) of the difference in the injection site pain score was contained within the equivalence margin of ±5. Other usability (overall impression and patient preference) and safety endpoints were also measured. Results: A total of 49 patients were enrolled and 48 patients completed the study. The mean injection site pain score was 2.3 in PFS vs. 2.0 in PFP immediately post-injection and 0.8 in PFS vs. 0.7 in PFP at 15–30 minutes post-injection. At both time points the score was equivalent between PFS and PFP: the 97.5% CI was (−0.99, 0.30) and (−0.47, 0.25) immediately and 15–30 minutes post-injection, respectively. The overall impression was also comparable between PFS and PFP. There were no patients who had an overall impression of extremely unfavorable and the proportion of patients who had a favorable impression was higher than that of unfavorable impression in both PFS and PFP. The overall preference for PFP (56.5%) was higher than PFS (30.4%) as presented in the Table. Both PFS and PFP were well tolerated and there were no serious treatment-emergent adverse events. Only one patient after administration of PFS experienced injection site reaction. Conclusions: The injection site pain score of PFS and PFP was comparable with overall preference rate higher for PFP. Both PFS and PFP were well tolerated with similar safety profiles. References: Shin D et al. Ann Rheum Dis. 2015; 74 (Suppl2: 459–460), FRI0110. Weinblatt ME et al. Arthritis Rheumatol. 2015; 67 (suppl 10). Shin D et al. Ann Rheum Dis 2016;75(Suppl2): 1005. Disclosure of Interest: J. Ghil Employee of: Samsung Bioepis Co., Ltd., J. Niebrzydowski Grant/research support from: Samsung Bioepis Co., Ltd., A. Zielińska Grant/research support from: Samsung Bioepis Co., Ltd., Y. Lee Employee of: Samsung Bioepis Co., Ltd.